Penerapan Budaya Organisasi Di Sekolah Dalam Menciptakan Sumber Daya Manusia (SDM) Yang Unggul - Lydia Amelia; Lukmawati Lukmawati; Muhammad Syaukani Siraj; Yuli Amelia; Yusril Ardiansyah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
. School as an organization certainly has a culture of organization which becomes an important role in the realization of the vision and mission of school. The culture of school organizations is the norms adopted and implemented by all components to achieve the vision and mission of the school effectively. This study aims to describe the culture of school organizations in SMK Negeri 1 Medan for preparing superior human resources and programs to support the culture of school. The approach of this study was quantitative observation, interview and documentation were used as the instruments of eliciting the data. The research subjects included elements of school residents, namely the deputy headmaster, teachers, and students. The results of this observation showed that (1) SMK Negeri 1 Medan has three superior cultures namely the culture of discipline, cooperation, and the culture of industrial work, (2) there are several programs for students in the application of school culture, (3) there are supporting and inhibiting factors for the realization of an effective school organization culture. According to observations, the culture of school organizations in SMK Negeri 1 Medan can be said to be effective.